FORMAÇÃO DE PROFESSORES DE LÍNGUA INGLESA NA PERSPECTIVA DECOLONIAL - BRUNO SILVA NASCIMENTO (2023)
The aim of this research was to broaden the understanding of english teacher education from the current decolonial perspective, through a bibliographic survey regarding english teacher education (EL) (TAKAKI, 2019; PESSOA, 2020; DUBOC, 2021; JORDÃO, 2013; VERONELLI; DAITCH, 2021, among others). I also set out to identify and analyze the works of scholars on traditional pedagogical praxiologies present in english teacher education and explore how these approaches can be reframed from a decolonial perspective, and to elaborate and analyze pedagogical activities in English language that promote criticality and decoloniality, considering differences/diversities. The discussions presented are supported by works of intellectuals of decolonial epistemologies, such as Walsh (2009, 2018), Castro-Gomez and Grosfoguel (2007), Maldonado-Torres (2007), Mignolo (2007, 2011, 2017), Quijano (2005, 2007, 2019), Sousa Santos (2018), among others. The perspectives in this work is in accordance with the requirements of the english teacher education program (and others). Contemplating these premises, the data generation took place in the applied field of linguistics and were analyzed in an educational research context, guided by critical literacy (MONTE, MÓR 2013), (JANKS, 2010), (MENEZES DE SOUZA, 2011), intercultural studies (WALSH, 2009), (SIQUEIRA, 2018) and critical language education (PESSOA; SILVA; FREITAS, 2021, MATTOS, 2018, DUBOC, 2018, PENNYCOOK, 2006). Through the bibliographic analysis, it was possible to observe praxiologies supported by updated decolonial and intercultural critical perspectives. Such theorizations show that we are exposed to a system of systematized practices, arising from the "colonial matrix of power" (MIGNOLO, 2010). In this context, this research instigates me to seek re-signification of the nature of the questions in order to give meaning to the english teacher education. Additionally, the results gathered in this research, such as the relevance of critical and reflective abilities in pedagogical practice, especially in academic contexts, and the potential for activities emphasizing decolonial critical theories, highlight efforts toward disruption aimed at ensuring the significance of the classes. However, this implies the need for a constant search for updating and continuous teacher education in a pluralistic and dynamic society, such as ours. It also emphasizes the importance of creativity, critical thinking, and ethics (TAKAKI; FERRAZ; MIZAN, 2019) in a critical approach to one's own beliefs and values.